Decoding Food Labels: Handouts for People with Food Allergies - Amy Simonne; Elizabeth Gollub (EDIS, 2017)
Full-page handouts for people with food allergies, to eggs, milk, peanuts, soy, and wheat. Lists for each allergen label terms to avoid and types of foods that contain it. Updated with photo illustrations.